Urban green : architecture for the future - Chambers, Neil B. ([S.l.] : Palgrave Macmillan, 2011)
Sustainable design is booming, but the men and women dedicated to reducing their carbon impact have lost sight of what they are trying to save: the natural world. Author Neil Chambers has been at the forefront of cutting-edge, sustainable architecture for years, and Urban Green is his revolutionary vision for bringing the power of the conservation and design movements together. He advocates looking to nature for the missing components of the green revolution: oysters that can clean water at up to 5 liters an hour; beavers that reshape their environments while simultaneously enriching ecosystems; and mountains that offer a new way of imagining how a city could be built. By designing our homes and cities in harmony with the natural world, we can take the next step in the sustainable revolution.
Keywords: Architecture--Environmental aspects; Environmental protection; Sustainable architecture